Questioning the Herderian ideal - Mishra, Pritipuspa (Routledge, 2021)
This chapter outlines Herder’s philosophy on language and the nation. It attempts to explain how even though the Herderian claim has been a monolingual one, curiously, at the same time, Herder has also been lauded as a trailblazer for promoting linguistic diversity. This chapter therefore is an exposition of the complexities that surround the Herderian ideal of language and nationalism. Why does the Herderian model continue to have valency in our modern contemporary world? How has the Herderian ideal of one nation-one language continued to survive beneath the uncomfortable resolution struck by new multilingual nations as they create fictions of a singular national mother tongue? How have different nations negotiated the Herderian ideal in different ways? This introduction draws from the contributions to this volume to address the afterlife of Herderian linguistic nationalism by looking at Herder across different times, space, and academic fields.